Erythrocytic α-Synuclein Species for Parkinson’s Disease Diagnosis and the Correlations With Clinical Characteristics - Yu, Zhenwei; Liu, Genliang; Li, Yang; Arkin, Ehsan; Zheng, Yuanchu; Feng, Tao (Frontiers in Aging Neuroscience, 2022)
Background Erythrocytes contain most of the peripheral α-synuclein (α-syn), which is the key pathological molecular of α-synucleinopathies including Parkinson’s disease (PD). Our objectives were to assess the efficiency of erythrocytic total and oligomeric α-syn levels as PD diagnostic biomarkers, and to identify the correlations between erythrocytic α-syn levels and physiological/psychiatrical assessment scales. Methods Home-brewed electrochemiluminescence assays were applied to assess the concentrations of erythrocytic total and oligomeric α-syn levels in a cohort including 124 patients with PD and 79 healthy controls (HCs). The correlations between erythrocytic α-syn levels and clinical measurements were assessed using Spearman’s rank test. Results Both the erythrocytic total and oligomeric α-syn levels were significantly higher in PD patients than HCs. The biomarkers adjusted for age and sex discriminated PDs from HCs well with 80% sensitivity, 89% specificity and 79% sensitivity, 83% specificity, respectively. Combining erythrocytic total and oligomeric α-syn levels by using binary logistic regression analysis with the controlling of age and sex generated a factor discriminates PDs from HCs with 88% sensitivity and 85% specificity. The erythrocytic total but not oligomeric α-syn levels adjusted for age and sex significantly correlated with anxiety scales and the MDS-UPDRS III scales in PD patients, respectively. Conclusion We showed the usefulness of erythrocytic total and oligomeric α-syn levels as biomarkers for PD. Our results also suggest the capability of erythrocytic α-syn as a potential pathological factor and therapeutic target for psychiatric symptoms in PD patients.